Urgensi Reformasi Perlindungan Merek dalam Dinamika Hukum Bisnis Indonesia - Hadi Muhammad Tajuddin; Romi Faslah (CV. ITTC INDONESIA, 2025)
This article examines the urgent need for reform in trademark protection within Indonesia’s evolving business and legal landscape, with a specific focus on micro, small, and medium enterprises (MSMEs). Trademarks are no longer limited to mere visual identifiers but have become key intangible assets that carry the reputation, competitive strength, and long-term sustainability of a business. Through a normative juridical approach and comprehensive literature review, this study evaluates the effectiveness of Law No. 20 of 2016 on Trademarks and Geographical Indications in practice. Despite the existence of a formal regulatory framework, challenges persist in the form of legal illiteracy, limited digital capacity, procedural complexities, and inadequate access to registration services for MSMEs. Furthermore, issues such as bad faith registration, weak public awareness, and the lack of an integrated technological system exacerbate the gap between regulation and implementation. The study proposes several strategic recommendations, including legal literacy campaigns, the development of a more user-friendly online registration system, and the creation of real-time trademark monitoring applications. These innovations are expected to increase the effectiveness of trademark protection, prevent disputes, and ultimately strengthen the competitiveness of Indonesian MSMEs in a globalized economy.